2017
DOI: 10.1055/s-0043-121629
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin and insulin-like Growth Factor Binding Protein-2 as Biomarkers of Disease Activity and Pathological Changes in Lupus Nephritis

Abstract: Background Systemic lupus erythematosus (SLE) is a chronic autoimmune inflammatory disease, characterised by the production of auto-antibodies and the formation of immune complexes due to the polyclonal activation of T and B lymphocytes, which results in tissue and organ damage. During inflammation, neutrophils and macrophages release serine proteases to cleave progranulin (PGRN) into granulin, which exerts its pro-inflammatory effects that counteract the anti-inflammatory effects of intact PGRN. It is suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…All these data indicate that IGFBP2 could indeed add diagnostic values significantly to current yardsticks. Furthermore, Goma et al, [16] showed a significant difference between the 3 groups with respect to IGFBP-2, except for ILGFBP-2, where no significant difference was noted between the CKD and control groups. There was a significant increase in IGFBP-2 with an increase in the SLEDAI score (p < 0.002 and p < 0.006 respectively).…”
Section: Fig 3 Receiver Operating Characteristics (Roc) Curve Analysismentioning
confidence: 91%
“…All these data indicate that IGFBP2 could indeed add diagnostic values significantly to current yardsticks. Furthermore, Goma et al, [16] showed a significant difference between the 3 groups with respect to IGFBP-2, except for ILGFBP-2, where no significant difference was noted between the CKD and control groups. There was a significant increase in IGFBP-2 with an increase in the SLEDAI score (p < 0.002 and p < 0.006 respectively).…”
Section: Fig 3 Receiver Operating Characteristics (Roc) Curve Analysismentioning
confidence: 91%